COMPARATIVE DIAGNOSTICS OF BRONCHOPULMONARY COMPLICATIONS IN YOUNG CHILDREN WITH WHOOPING COUGH - Sultonov, Ravshan; Qurbonov, Tuqtash; Qurbonova, Gulnoza (Medical science of Uzbekistan, 2025)
Whooping cough remains one of the leading causes of infant mortality worldwide. This article presents a comparative diagnosis of bronchopulmonary complications in young children infected with respiratory syncytial virus and pertussis virus. The study was conducted on 50 children with pertussis at the central polyclinic of Termez city, Surkhandarya region, during 2023-2024. All 50 children with whooping cough were divided into age groups as follows: 1-year-old children formed the 1st group, 2-year-old children formed the 2nd group, and 3-year-old children formed the 3rd group. When examining the disease by gender in the study: Bronchopulmonary complications in boys were categorized into subgroups based on the results of objective and instrumental examinations and were assessed as follows: Bronchopneumonia in 18 (36%) patients, acute bronchitis in 16 (32%) patients, laryngitis in 6 (12%) patients, and bronchitis+laryngitis in 9 (18%) patients. In girls, bronchopulmonary complications were studied by subgroups as follows: bronchopneumonia was observed in 6 (12%) patients, acute bronchitis in 16 (32%) patients, laryngitis in 15 (30%) patients, and bronchitis+laryngitis in 13 (26%) patients. In conclusion, among the bronchopulmonary complications in children with whooping cough, bronchopneumonia was observed in 38% of boys, while acute bronchitis was seen in 32% of girls. It was found that 30% of all examined patients were not vaccinated at all, of which 10% had not yet reached the age for vaccination. Whooping cough tends to be severe in children, mainly in early childhood (1-3 years old), due to incomplete vaccination against the disease. These cases require a special therapeutic approach.